2019
DOI: 10.1186/s12906-019-2616-3
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide attenuates lipopolysaccharide-induced inflammatory responses in human endothelial cells: involvement of NF-κB pathway

Abstract: Background Endothelial cell inflammation is a central event in the pathogenesis of numerous cardiovascular diseases, including sepsis and atherosclerosis. Triptolide, a principal bioactive ingredient of Traditional Chinese Medicine Tripterygium wilfordii Hook.F., displays anti-inflammatory actions in vivo. However, the mechanisms underlying these beneficial effects remain undetermined. The present study investigated the effects and possible mechanisms of triptolide on li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 32 publications
0
26
0
2
Order By: Relevance
“…2 The First Affiliated Hospital of Nanjing Medical University, Nanjing 210029, China. 3 Beijing Information Science & Technology University, Beijing 100192, China.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The First Affiliated Hospital of Nanjing Medical University, Nanjing 210029, China. 3 Beijing Information Science & Technology University, Beijing 100192, China.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Atherosclerosis, a complex cardiovascular disease, has been reported as a chronic inflammatory disease by the increasing studies [1,2]. At different stages of atherosclerosis, the infiltration of various inflammatory cells, such as T cells, mast cells and macrophages, into the atherosclerotic plaques is one of the main characteristics of atherosclerosis [3]. Subsequently, the migration and proliferation of vascular smooth muscle cells (VSMCs), which attribute to the formation of neointima and atherosclerotic plaques, could be promoted by these infiltrated inflammatory cells in company with the resident vascular wall cells via the secretion of cytokines and growth factors [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…It remains a great challenge to alleviate sepsis-induced endothelial injury. Moreover, recently some herbal medicines have been found to improve endothelial dysfunction and reduce inflammatory responses in LPS-induced HUVECs [8,9]. Therefore, more effective drugs are needed for protection against endothelial injury in sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…These properties of triptolide are explained by the inhibition of the production of cytokines such as TNF-alpha, IL-1, IL-6, IL-8 and phagocytosis of phagocytes. It has been shown that these effects of triptolide are closely related to NF-κB activity (7,8,20). Gray et al (21) reported that lung and liver damage occur due to the activation of NF-κB in the presence of pancreatitis-induced SIRS.…”
Section: Discussionmentioning
confidence: 99%
“…Triptolide is extracted from the roots of Chinese herb Tripterygium wilfordii and is known as an NF-κB inhibitor. Previous studies have shown that triptolide has a broad-spectrum therapeutic potential due to its immunosuppressive, anti-inflammatory and anti-tumor properties (6)(7)(8). Our experimental study aimed to investigate the healing effects of single dose-triptolide treatment in the early phase of cerulein-induced severe acute pancreatitis in rats.…”
Section: Introductionmentioning
confidence: 99%